Identification of catalytic sites in cobalt-nitrogen-carbon materials for the oxygen reduction reaction. Issue 1 (December 2017) - Zitolo, Andrea; Ranjbar-Sahraie, Nastaran; Mineva, Tzonka; Li, Jingkun; Jia, Qingying; Stamatin, Serban; Harrington, George; Lyth, Stephen; Krtil, Petr; Mukerjee, Sanjeev; Fonda, Emiliano; Jaouen, Frédéric
Abstract Single-atom catalysts with full utilization of metal centers can bridge the gap between molecular and solid-state catalysis. Metal-nitrogen-carbon materials prepared via pyrolysis are promising single-atom catalysts but often also comprise metallic particles. Here, we pyrolytically synthesize a Co–N–C material only comprising atomically dispersed cobalt ions and identify with X-ray absorption spectroscopy, magnetic susceptibility measurements and density functional theory the structure and electronic state of three porphyrinic moieties, CoN4 C12, CoN3 C10, porp and CoN2 C5 . The O2 electro-reduction andoperando X-ray absorption response are measured in acidic medium on Co–N–C and compared to those of a Fe–N–C catalyst prepared similarly. We show that cobalt moieties are unmodified from 0.0 to 1.0 V versus a reversible hydrogen electrode, while Fe-based moieties experience structural and electronic-state changes. On the basis of density functional theory analysis and established relationships between redox potential and O2 -adsorption strength, we conclude that cobalt-based moieties bind O2 too weakly for efficient O2 reduction. Nitrogen-doped carbon materials with atomically dispersed iron or cobalt are promising for catalytic use. Here, the authors show that cobalt moieties have a higher redox potential, bind oxygen more weakly and are less active toward oxygen reduction than their iron counterpart, despite similar coordination.